2017
DOI: 10.1155/2017/9495783
|View full text |Cite|
|
Sign up to set email alerts
|

Successful Pelvic Resection for Acetabular Hydatidosis

Abstract: Background Hydatidosis of the bone is a rare occurrence (0.9 to 2.5% of all localization of the disease). In those occurrences, the pelvic bone is the second most frequent localization. Curative treatment of pelvic bone hydatidosis is difficult and a consensus is yet to be found. Clinical Case We report a case of hydatidosis of the ischium, extended to the homolateral hip. The patient was treated through hip resection using patient-specific cutting guides, followed by total hip reconstruction. Albendazole was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Daniel et al reported a case of pelvic CE extending to the hip. After hip resection combined with total hip arthroplasty supplemented by perioperative medication, the patient had no signs of recurrence or sepsis at 1-year postoperative follow-up, but he required a walker as a mobility aid ( Daniel et al, 2017 ). As can be seen, the outcome of pelvic-joint infection is very serious.…”
Section: Treatment: Radical Resection and Drug Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Daniel et al reported a case of pelvic CE extending to the hip. After hip resection combined with total hip arthroplasty supplemented by perioperative medication, the patient had no signs of recurrence or sepsis at 1-year postoperative follow-up, but he required a walker as a mobility aid ( Daniel et al, 2017 ). As can be seen, the outcome of pelvic-joint infection is very serious.…”
Section: Treatment: Radical Resection and Drug Therapymentioning
confidence: 99%
“…Improved after 6 months Lumbar vertebra and sacral vertebra (Majmundar et al, 2019;Sharma et al, 2020;Trifa and Maamri, 2021) Debridement Femoral bone (Gautam et al, 2018;Salman et al, 2018;Dathik et al, 2019;Fröschen et al, 2019;Masmoudi et al, 2019;Ramteke et al, 2019;Oueslati et al, 2020;Ahmady-Nezhad et al, 2022) Resection of the lesion; fixation; resection of the lesion; mobility aid (Daniel et al, 2017). As can be seen, the outcome of pelvic-joint infection is very serious.…”
Section: Surgerymentioning
confidence: 99%
“…In the article titled “Successful Pelvic Resection for Acetabular Hydatidosis” [1], there was an error in the authors' name format as they were reversed. The correct author list and affiliations are shown above.…”
mentioning
confidence: 99%